Analisis manfaat sistem irigasi pompanisasi terhadap pendapatan petani di Kecamatan Rimba Melintang Kabupaten Rokan Hilir - Darmawan, Tengku Ilham; Kadir, Hainim; ', Eriyati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the pumping Irrigation Benefit Analysis System Against Farmers Income. Method of analysis used by the authors in this study is descriptive methods and data used is primary data and secondary data. The analysis was performed on several aspects: fixed costs, variable costs, total costs, harvested area, production, price, total revenue, and revenue before and after the pumping. From the results of research in each area increased before and after pumping. Income of farmers in land 1 ha before pumping is Rp. 8,950,000. - And after pumping of Rp. 18,750,000. -, In the land of 1.5 prior to the pumping of Rp. 13.425.000 - After pumping increased by Rp. 28.125.000 - And on 2 hectares of land before pumping of Rp. 17.900.000 - And after the pumping increased by Rp. 37,500,000. –Keywords: Income, Farmers, Irrigation pumping and Benefits System.